Potensi Clean Development Mechanism pada Pembangkit Mikrohidro 120 KW - - Gunawan; Didiek Eko Budi Santoso; M. Subchan (MEDIA ELEKTRIKA, 2010)
Polential of Micro Hydro Power in remote areas is the most realistic as the primary energy for electricity generation. Potential energy become a growing alternative for the region to diversify its electricity supply. The issue of global warming that encourages the use of renewable energy in an effort to prevent damage to the natural speed of following up a global agreement under the Kyoto Protocal. One program in the reduction of exhaust emissions is the Clean Development Mechanism (CDM). Through this concept all the activities of energy usage can be measured and calculated potential relation with the exhaust emissions.CDM potential measurement begins by defining the instrument to be used. MHP is the power output is a fixed value that is used as a reference that will measure the impact if generated by fossil energy utilization. This step is an approach that shows how the potential for greenhouse gas emissions that can be prevented if the electrical power needs supplied by renewable energy-based generation.The sample of study is MHP Cinta Mekar in Subang district indicates that this location was proposed as a viable small-scale projects under the CDM. MHP is able to produce electrical energy of 120 KW. CDm potential is calculated are the reduction of fossil energy consumption of 1.5 tons per day. In addition to equality of use of fossil fuels for electrical potential energy also has the potential to reduce environmental pollution by 1474.2 tons / year of CO2.Keyword : CDM, MHP, Energy, Pollution